Renal function outcomes and kidney biopsy features of living kidney donors with hypertension. Issue 6 (30th March 2021) - Merzkani, Massini A.; Mullan, Aidan; Denic, Aleksandar; D'Costa, Matthew; Iverson, Ryan; Kremers, Walter; Alexander, Mariam P.; Textor, Stephen C.; Taler, Sandra J.; Stegall, Mark D.; Augustine, Joshua; Issa, Naim; et al.
Abstract: Background: The medium‐ to long‐term outcomes of living kidney donors with hypertension compared to normotensive donors are not well understood, especially with the recent changes in hypertension guidelines. Methods: We studied a cohort of 950 living kidney donors using different definitions of hypertension based on either ≥140/90 or ≥130/80 mmHg thresholds and based on either office or ambulatory blood pressure readings. Microstructural features on kidney biopsy at the time of donation were compared using different definitions of hypertension. Results: After adjusting for years of follow‐up, age, sex, and baseline eGFR, hypertension (by any definition) did not significantly predict an eGFR < 45 ml/min/1.73 m 2 at a median follow‐up of 10 years postdonation, though there was a borderline association with ambulatory blood pressure ≥ 130/80 mmHg predicting a 40% decline in eGFR (OR = 1.53, 1.00–2.36; p = .051). Proteinuria was predicted by office blood pressure ≥ 140/90 mmHg and by nondipper profile on nocturnal ambulatory blood pressure measurements. At the time of donation, larger glomeruli and arterial hyalinosis on biopsy were associated with hypertension defined by either ≥140/90 or ≥130/80 mmHg (by office or ambulatory measurements). Nocturnal nondipper status was associated with larger glomeruli size but not arteriolar hyalinosis when compared to dippers. Conclusions: In programs that accept donors with controlled hypertension, various definitions of hypertension are associated with histological findings in the donated kidney, but none predict a clinically significant decline in kidney function 10 years after donation. These data support allowing healthy individuals with controlled hypertension to donate a kidney. However, donors with office hypertension (≥140/90 mmHg) and nondippers (regardless of hypertension status) are at greater long‐term risk for proteinuria, and particularly for these donors, longer follow‐up is warranted.